The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5897/jcems2017.0293
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic oxidation of 17 -Ethinylestradiol by UV-activated TiO2 in batch and continuous-flow reactor

Abstract: In this study, the photocatalytic oxidation by UV-activated TiOat pH 7. Ultraviolet-C (UVC) photolysis presented a removal of 40% in 2 h at pH 7 with the system operating in batch mode. Operating as a sequencing batch, the reactor showed remarkable efficiency in the removal of EE2 in a short period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The maximum photolysis removal was of 89% for E2 and EE2 under UVC radiation in 120 min, while removal in the same conditions for UVA was of approximately 28%. Carvalho et al [25] observed E2 removals (5 mg•L -1 ) of 88% and 75%, respectively, by UVC and UVA photolysis. Similar results were obtained by Liu et al [26], when evaluating E2 degradation, where 60% degradation using UVC radiation was obtained, while degradation under UVA radiation was negligible.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum photolysis removal was of 89% for E2 and EE2 under UVC radiation in 120 min, while removal in the same conditions for UVA was of approximately 28%. Carvalho et al [25] observed E2 removals (5 mg•L -1 ) of 88% and 75%, respectively, by UVC and UVA photolysis. Similar results were obtained by Liu et al [26], when evaluating E2 degradation, where 60% degradation using UVC radiation was obtained, while degradation under UVA radiation was negligible.…”
Section: Resultsmentioning
confidence: 99%
“…To address this problem, several strategies have been implemented to remediate this hormone EE2 as a micropollutant alongside other related environmentally persistent toxicants. Different treatment techniques such as biological degradation, advanced oxidation process, catalytic reduction, photocatalysis, and adsorption method have been investigated [11][12][13][14][15][16][17][18][19]. Out of these methods, the elimination of EDCs by adsorption process has proven to be more beneficial due to low concentration target compounds, simplicity, and cost-effectiveness [20].…”
Section: Introductionmentioning
confidence: 99%